The Language of Women's Pain: Ideology and Critical Cultural Competencies in Pain Literacy - Taylor, Mary Anne; Glowacki, Elizabeth M. (Frontiers in Communication, 2020)
This manuscript is concerned with a key tension in health communication: How women’s pain is rhetorically constructed and culturally consumed. To date, there has been much research devoted to communicating the language of pain, rather, pain’s expressibility (Scarry, 1985), as well as the construction of health narratives from private pain into public action (Kimball, 2000). Building on that literature, we make a rhetorical turn, and argue for a more critical rhetorical approach to pain literacy. To that end, the primary goal of this essay is to explore the rhetorical nuances and ideological limitations in pain literacy and pain response, from the point of when pain is expressed to how that expression is perceived. Through a critical cultural lens, we critique dominant narratives of pain, and argue for an intersectional heuristic of rhetorical care that promotes cultural competency and awareness to bridge gaps in the expression and perception of pain literacy.